Demand-side economics in times of high debt: The case of the European Union - Monika Köppl-Turyna; Hanno Lorenz (Agenda Austria, 2016)
We analyze the effectiveness of an increase in government consumption for stimulating growth for diverse levels of public debt in the European Union. We conclude, that growth rate can be stimulated in the short run by an increase in government consumption but only at low levels of public debt. Moreover, we find that an increase in intermediate consumption is more effective than an increase in compensation of public employees in stimulating output growth.
Keywords: E62; H30; H50; H63; 330; growth; fiscal stimulus; government consumption; public debt